2021
DOI: 10.1111/jre.12929
|View full text |Cite
|
Sign up to set email alerts
|

Influences of periodontitis on hippocampal inflammation, oxidative stress, and apoptosis in rats

Abstract: Background and aim:The hippocampus, which has a central role in cognitive and behavioral activities, is one of the most sensitive parts of the brain to systemic inflammatory diseases. This animal study aims to comprehensively investigate the possible inflammatory, oxidative, and apoptotic effects of periodontitis on the hippocampus.Methods: Sixteen male Sprague-Dawley rats were randomly assigned to two groups: control and experimental periodontitis (Ep). In the Ep group, periodontitis was induced by placing 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(164 reference statements)
1
3
0
Order By: Relevance
“…Therefore, this study chose an 8‐week ligature‐induced CP model. Consistent with previous studies (Kose et al, 2021; Lin et al, 2017), we observed extensive bone destruction in the CP mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, this study chose an 8‐week ligature‐induced CP model. Consistent with previous studies (Kose et al, 2021; Lin et al, 2017), we observed extensive bone destruction in the CP mice.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with the mousePorphyromonas gingivalis infection model, the ligature-induced periodontitis model may reflect a broader pathogenesis of bone loss and inflammation(de Molon et al, 2014;Lin et al, 2017). In addition, experimental long ligation models are usually preferred in studies that assess the chronic systemic effects of periodontitis on various organ systems(Kose et al, 2021). Therefore, this study chose an 8-week ligature-induced CP model.…”
mentioning
confidence: 99%
“…Our serum detection results using the reagent kits showed that the T-AOC and expressions of antioxidant enzymes, including CAT, SOD, and GSH-Px, in the Perio+MT-CD group were elevated in contrast to the Perio group (Figure I, J, L, and M). Malondialdehyde (MDA), a key indicator of oxidative damage to cell structure membrane phospholipids, exhibited a notable increase in the Perio group, signifying significant oxidative damage in periodontal tissue . The increase in the level of MDA in untreated periodontitis indicates a significant degree of oxidative damage in periodontal tissue (Figure K).…”
Section: Results and Discussionmentioning
confidence: 98%
“…Malondialdehyde (MDA), a key indicator of oxidative damage to cell structure membrane phospholipids, exhibited a notable increase in the Perio group, signifying significant oxidative damage in periodontal tissue. 73 The increase in the level of MDA in untreated periodontitis indicates a significant degree of oxidative damage in periodontal tissue (Figure 7K). In contrast, MT-CDs demonstrated a significant inhibitory effect on this process.…”
Section: Impact Of Mt-cds For Promoting Osteogenesis On Mc3t3-e1 and ...mentioning
confidence: 94%